HUBUNGAN TINGKAT KARIES GIGI PADA ANAK PRA SEKOLAH TERHADAP STUNTING DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Budiarti, Indah; Andriyani, Desi; Murwaningsih, Sri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
Stunting is a condition that disrupts the growth and development of children caused by a lack of adequate nutritional intake and frequent infections. This condition is characterized by the child's height being below normal limits. Stunting that occurs at the preschool stage (first five years) can continue until school. In addition to factors related to pregnancy and childbirth, factors such as the environment, diet, and health history of the child also have a significant influence on the development of stunting in children during childhood.The risk of stunting in children can be divided into five groups of factors, namely: Maternal infections and nutritional problems, Adolescent mothers and short birth intervals, Premature birth and growth disorders, Fetal growth. If tooth decay is not treated, it can result in eating problems and sleep quality. , painful and requires ongoing treatment. Tooth decay in children will feel pain in the area of tooth decay. Therefore, this will reduce food consumption. A decrease in a child's food intake over a long period of time will have an impact on his nutritional status. This research method uses an observational research design with a cross sectional method and data collection uses a questionnaire to examine the level of dental caries in stunted children in the area supported by the Gedong Tataan Pesawaran Community Health Center in 2023.This research was research conducted from July to August with a total of 69 respondents using population sampling techniques. Based on the results of the analysis of the effect of stunting on the level of tooth decay, the decision taken was based on a p-value of 0.000 (p-value < 0.05), the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. This shows that there is a significant relationship or difference between the independent variable and the dependent variable in the study. It has an influence between developmental delays and the severity of caries.